2014
DOI: 10.1111/joor.12232
|View full text |Cite
|
Sign up to set email alerts
|

Earlier depression and later‐life self‐reported chewing difficulties: results from the Whitehall II study

Abstract: This study aimed to assess, whether depression in adulthood was associated with self-reported chewing difficulties at older age, and examine whether the strength of the association differed according to the number of depression episodes in earlier adult life. We used Whitehall II study data from 277 participants who completed a questionnaire in 2011. Depression was measured with the Center for Epidemiologic Studies Depression Scale (CES-D) in 2003 and 2008. The association between CES-D depression and self-rep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
21
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(22 citation statements)
references
References 19 publications
1
21
0
Order By: Relevance
“…These factors were related to only SMF, so that this result was considered to relate to the disagreement of results that the subjective assessment was “poor” although the objective assessment was “good”. In previous studies, SMF has been reported to be susceptible to the psychological state, while mental stress and psychiatric drugs have been reported to cause mouth dryness . In other words, cooperation with other clinical department, such as a change in drug and or psychological approach, may be needed to reduce SMF that are affected by psychogenic factors.…”
Section: Discussionmentioning
confidence: 99%
“…These factors were related to only SMF, so that this result was considered to relate to the disagreement of results that the subjective assessment was “poor” although the objective assessment was “good”. In previous studies, SMF has been reported to be susceptible to the psychological state, while mental stress and psychiatric drugs have been reported to cause mouth dryness . In other words, cooperation with other clinical department, such as a change in drug and or psychological approach, may be needed to reduce SMF that are affected by psychogenic factors.…”
Section: Discussionmentioning
confidence: 99%
“…There have been three reports on the association between chewing difficulty and symptoms of depression . The Whitehall II study was a prospective closed‐cohort study with a small sample size (N = 227), and the results cannot be generalized .…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, few studies have investigated the association between chewing difficulty and depression. There is some evidence of this association, although it is from one study with a small sample size and another study in participants aged 65 and older …”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Aljameel et al . . reported that individuals who experienced depression in their earlier adulthood were at greater risk of having chewing difficulties at an older age.…”
Section: Discussionmentioning
confidence: 99%